2003
DOI: 10.1523/jneurosci.23-33-10495.2003
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and Octopamine Differentiate between Aversive and Appetitive Olfactory Memories inDrosophila

Abstract: The catecholamines play a major role in the regulation of behavior. Here we investigate, in the fly Drosophila melanogaster, the role of dopamine and octopamine (the presumed arthropod homolog of norepinephrine) during the formation of appetitive and aversive olfactory memories. We find that for the formation of both types of memories, cAMP signaling is necessary and sufficient within the same subpopulation of mushroom-body intrinsic neurons. On the other hand, memory formation can be distinguished by the requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
972
9
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 776 publications
(1,028 citation statements)
references
References 45 publications
44
972
9
3
Order By: Relevance
“…There is abundant evidence suggesting that Kenyon cells participate in insect olfactory learning in fruit-flies (Akalal, Wilson, Zong, Tanaka, Ito, & Davis, 2006;Davis, 2005;Schwaerzel et al, 2003) and honey bees (Cano Lozano et al, 2001), but the types of ACh receptors used by Kenyon cells participating in olfactory learning have not been specified in any species of insects. This study is the first to suggest that Kenyon cells possessing MEC-sensitive nAChR or their postsynaptic neurons in the MB play critical roles in olfactory conditioning, providing a basis for extending our pharmacological and electrophysiological studies of molecular and neural circuit mechanisms of olfactory learning.…”
Section: Kenyon Cells or In Neurons Downstream Of The Kenyon Cells Pomentioning
confidence: 99%
See 2 more Smart Citations
“…There is abundant evidence suggesting that Kenyon cells participate in insect olfactory learning in fruit-flies (Akalal, Wilson, Zong, Tanaka, Ito, & Davis, 2006;Davis, 2005;Schwaerzel et al, 2003) and honey bees (Cano Lozano et al, 2001), but the types of ACh receptors used by Kenyon cells participating in olfactory learning have not been specified in any species of insects. This study is the first to suggest that Kenyon cells possessing MEC-sensitive nAChR or their postsynaptic neurons in the MB play critical roles in olfactory conditioning, providing a basis for extending our pharmacological and electrophysiological studies of molecular and neural circuit mechanisms of olfactory learning.…”
Section: Kenyon Cells or In Neurons Downstream Of The Kenyon Cells Pomentioning
confidence: 99%
“…In the cockroach, octopaminergic neurons with more or less similar morphology have been found (Sinakevitch, Niwa, & Strausfeld, 2005) and we speculate that some of these neurons convey sucrose US to various protocerebral areas. Roles of octopaminergic neurons for acquisition (Farooqui, Vaessin, & Smith, 2004;Nakatani, Matsumoto, Mori, Hirashima, Nishino, Arikawa, & Mizunami, 2009;Schroll, Riemensperger, Bucher, Ehmer, Voller, Erbguth, Gerber, Hendel, Nagel, Buchner, & Fiala, 2006;Schwaerzel et al, 2003;Unoki, Matsumoto, & Mizunami, 2005 In honey bees and fruit-flies, it has been suggested that both the MB and AL are the sites of association of olfactory CS and sucrose US for olfactory conditioning (Davis, 2005;Hammer & Menzel, 1998;Thum et al, 2007). For example, pharmacological inactivation of the MB during the differential conditioning trials was not impaired olfactory memory acquisition, suggesting that output region of MB do not involve in the olfactory differential conditioning (Devaud, Blunk, Podufall, Giurfa, & Grünewald, 2007).…”
Section: Neural Pathways Mediating Conditioned Olfactory Responses Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the short-term odor memory of Drosophila, the intrinsic neurons of the mushroom body (MB), the Kenyon cells (KCs), are supposed to be a converging site of olfactory information and electric shock punishment or sugar reward (Schwaerzel et al, 2003;Gerber et al, 2004) (see Fig. 1 A).…”
Section: Introductionmentioning
confidence: 99%
“…Biogenic amines control endocrine and exocrine secretion (Just and Walz, 1996;Marg et al, 2004), the contraction properties of muscles, the activity of neurons (for a review, see Bicker and Menzel, 1989), and the generation of motor patterns (Claassen and Kammer, 1986). In addition, certain biogenic amines are involved in learning and the formation of memory (Schwaerzel et al, 2003; for reviews, see: Meller and Davis, 1996;Hammer, 1997). Biogenic amines mediate these diverse cellular and physiological effects by binding to G protein-coupled receptors (GPCRs; for reviews, see : Vernier et al, 1995;Baumann, 2001, 2003;Park and Adams, 2005), which are integral membrane proteins that sense and transduce extracellular signals into specific cellular responses.…”
mentioning
confidence: 99%